Response to Domestic Violence in the Quincy, Massachusetts, District Court, 1995-1997 - Buzawa, Eve Schlesinger ([Verlag nicht ermittelbar], 2001)
The Quincy, Massachusetts, District Court initiated an aggressive, pro-intervention strategy for dealing with domestic violence cases in 1986. This study was funded to examine the workings of this court and its impact on the lives of victims. The four main goals of the research were: (1) to describe the workings of the primary components of this model jurisdiction in its response to domestic violence, specifically (a) what the police actually did when called to a domestic violence incident, (b) decisions made by the prosecutor's office and the court in their handling of these incidents, (c) how many victims talked to a victim advocate, and (d) how many offenders received batterer treatment and/or were incarcerated, (2) to describe the types of incidents, victims, and offenders seen in a full enforcement jurisdiction to determine if the types of cases coming to attention in such a setting looked similar to cases reported in studies from other jurisdictions, (3) to interview victims to hear directly about their experiences with a model court, and (4) to examine how well this model jurisdiction worked in preventing revictimization. Data used in this study were based on domestic violence cases that resulted in an arrest and arraignment before the Quincy District Court (QDC) during a seven-month study period. Six types of data were collected for this study: (1) The offender's criminal history prior to the study and for one year subsequent to the study incident were provided by the QDC's Department of Probation from the Massachusetts Criminal Records System Board. (2) Civil restraining order data were provided by the Department of Probation from a statewide registry of civil restraining orders. (3) Data on prosecutorial charges for up to three domestic violence-related charges were provided by the Department of Probation. (4) Data on defendants who attended batterer treatment programs were provided by directors of two such programs that served the QDC. (5) Police incident reports from the seven departments served by the QDC were used to measure the officer's perspective and actions taken relating to each incident, what the call for service involved, characteristics of the incident, socio-demographics of the participants, their narrative descriptions of the incident, and their stated response. (6) Interviews with victims were conducted one year after the occurrence of the study incident. Variables from administrative records include date and location of incident, number of suspects, age and race of victims and offenders, use of weapons, injuries, witnesses, whether there was an existing restraining order and its characteristics, charges filed by police, number and gender of police officers responding to the incident, victim's state at the time of the incident, offender's criminal history, and whether the offender participated in batterer treatment. The victim survey collected data on the victim's education and employment status, current living arrangement, relationship with offender, how the victim responded to the incident, how afraid the victim was, victim's opinions of police and the prosecutor, victim's sense of control, satisfaction with the court, victim's past violent relationships and child sexual abuse, victim's opinions on what the criminal justice system could do to stop abuse, and whether the victim obtained a restraining order.